AI for medical imaging goes deep. (May 2018) - Ting, Daniel; Liu, Yong; Burlina, Philippe; Xu, Xinxing; Bressler, Neil; Wong, Tien
An artificial intelligence (AI) using a deep-learning approach can classify retinal images from optical coherence tomography for early diagnosis of retinal diseases and has the potential to be used in other image-based medical diagnoses.